Application of the Game Theory in Modelling Greek Negotiation with Creditors in 2015 - Mesjasz, Lidia; Mesjasz, Czesław (Studia Oeconomica Posnaniensia, 2017)
The concepts borrowed from the game theory are applied for the construction of the mathematical models of processes of negotiations and as a basis for creating analogies and metaphors, which, in turn, are applied for description, causal analysis and prediction. The aim of the paper is to use the concepts drawn from the game theory to model negotiations between Greece and its creditors in the year 2015, which was of crucial importance for averting the danger of a serious crisis in the European Union, and even on a global scale. In addition, the last round of negotiations of Greece with its creditors reflects the complexity of the country's debt problem and includes both the possibility of a solution for the crisis and as a sign of further tensions. As a basis for the discussion the concepts of "brinkmanship", "prisoner's dilemma" and "chicken" was adopted.